New Insights into the Taxonomy of Bacteria in the Genomic Era and a Case Study with Rhizobia. (21st May 2022) - Ferraz Helene, Luisa Caroline; Klepa, Milena Serenato; Hungria, Mariangela
Abstract : Since early studies, the history of prokaryotes taxonomy has dealt with many changes driven by the development of new and more robust technologies. As a result, the number of new taxa descriptions is exponentially increasing, while an increasing number of others has been subject of reclassification, demanding from the taxonomists more effort to maintain an organized hierarchical system. However, expectations are that the taxonomy of prokaryotes will acquire a more stable status with the genomic era. Other analyses may continue to be necessary to determine microbial features, but the use of genomic data might be sufficient to provide reliable taxa delineation, helping taxonomy to reach the goal of correct classification and identification. Here we describe the evolution of prokaryotes' taxonomy until the genomic era, emphasizing bacteria and taking as an example the history of rhizobia taxonomy. This example was chosen because of the importance of the symbiotic nitrogen fixation of legumes with rhizobia to the nitrogen input to both natural ecosystems and agricultural crops. This case study reports the technological advances and the methodologies used to classify and identify bacterial species and indicates the actual rules required for an accurate description of new taxa.